Pollution studies in the Río Santiago Basin, tributary of the Río de La Plata Estuary : Preliminary risk assessment evaluation - Ronco, Alicia Estela (1993)
Recent developments in the field of ecotoxicological effects assessment of pollutants on aquatic systems make use of methods founded on statistical principles and requirements (Kooijman 1987; Van Straalen & Denneman 1989). Van Straalen and Kooijman methods estimate a hazardous concentration for p percent of species in a community (HCp) at a chosen protection level. Evaluations on the application of the methodology to different toxic compounds and test species using both chronic and acute toxicity data have been undertaken (Van Leeuwen 1990).